2019
DOI: 10.3389/fpsyt.2019.00872
|View full text |Cite
|
Sign up to set email alerts
|

Neurobiology of Aggressive Behavior—Role of Autoantibodies Reactive With Stress-Related Peptide Hormones

Abstract: Adrenocorticotropic hormone together with arginine vasopressin and oxytocin, the neuropeptides regulating the stress response and the hypothalamic-pituitary-adrenal axis activity, are known to modulate aggressive behavior. The functional role of the adrenocorticotropic hormone immunoglobulin G autoantibodies in peptidergic signaling and motivated behavior, including aggression, has been shown in experimental and in vitro models. This review summarizes some experimental data implicating autoantibodies reactive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 93 publications
2
5
0
Order By: Relevance
“…We did not observe an effect of aMSH treatment on R. imitator tadpoles, which reinforces findings in O. pumilio tadpoles that aggression and hunger are decoupled [44]. Aggression studies with ACTH also suggest a role for promoting aggression, where mice injected with ACTH attack intruders more quickly [80], and rats bred for low anxiety had higher plasma corticotropin (ACTH) and subsequently exhibited higher levels of aggression as compared to high anxiety-bred or control rats [81]. Interestingly, injecting mice daily with ACTH will initially lead to an increase in aggression, but causes a decrease in aggressive action by days 4-7 [82].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…We did not observe an effect of aMSH treatment on R. imitator tadpoles, which reinforces findings in O. pumilio tadpoles that aggression and hunger are decoupled [44]. Aggression studies with ACTH also suggest a role for promoting aggression, where mice injected with ACTH attack intruders more quickly [80], and rats bred for low anxiety had higher plasma corticotropin (ACTH) and subsequently exhibited higher levels of aggression as compared to high anxiety-bred or control rats [81]. Interestingly, injecting mice daily with ACTH will initially lead to an increase in aggression, but causes a decrease in aggressive action by days 4-7 [82].…”
Section: Discussionsupporting
confidence: 84%
“…We did not observe an effect of aMSH treatment on R. imitator tadpoles, which reinforces findings in O. pumilio tadpoles that aggression and hunger are decoupled [44]. Aggression studies with ACTH also suggest a role for promoting aggression, where mice injected with ACTH attack intruders more quickly [80],…”
Section: Neuromodulators Of Aggression Vary Across Development and Sp...supporting
confidence: 85%
“…Unlike CSF neuropeptide levels, plasma neuropeptide levels do not reflect directly central nervous system neuropeptides concentrations; hence, the absence of association in this study may have been unavoidable. Considering previous preclinical 5,9,10 and clinical 4,6–8 reviews, regional structural or functional brain alterations related to neuropeptides could occur in patients with psychiatric disorders although our data suggested that such alterations may not be reflected in plasma neuropeptide levels. Molecular imaging (e.g., positron emission and single photon emission computed tomography) studies targeting neuropeptides in the brain may explain the pathomechanism of neuropeptides in patients with psychiatric disorders, although such studies are still scarce in preclinical 60,61 and clinical stages 62–64 …”
Section: Discussionmentioning
confidence: 56%
“…However, a recent meta-analysis showed only marginal support for the dual-hormone hypothesis for risk taking, aggression, dominance, and psychopathy (Dekkers et al, 2019 ). Other physiological factors have also been investigated as potential moderators (e.g., neuropeptides; Vaeroy et al, 2019 ). Psychological factors may also play a role in the relation between cortisol and aggression.…”
Section: Introductionmentioning
confidence: 99%